Promise of Synbiotic in Gut-Kidney Axis - Josephine Herwita Atepela (PT Kalbe Farma Tbk., 2024)
Human microbiota plays a role in protecting human health. Change in the microbial composition will lead to an imbalance between the beneficial and potentially harmful bacteria, leading to “dysbiosis”. The pathogenic interconnection between gut microbiota and kidney diseases is called the gut–kidney axis, which is implicated in a wide range of clinical manifestations such as CKD (chronic kidney disease), AKI (acute kidney injury), hypertension, nephrolithiasis, IgA nephropathy, hemodialysis, and peritoneal dialysis. Synbiotic, a mixture of probiotics and prebiotics are reported to be beneficial in human health via the gut-kidney axis.